Kinetics study and modelling of sorghum grain hydration - Danielli Alessandra Reino Olegário da Silva; Luiz Mário de Matos Jorge; Regina Maria Matos Jorge (Revista Ciência Agronômica)
ABSTRACT Sorghum grains were soaking to evaluate the effects of time and temperature on moisture and process modelling was maked with different mathematical equations. Then, sorghum BRS 310 and BRS 655 were hydrated at 30 °C, 40 °C, 50 °C and 60 °C, for 12 hours. The hydration kinetics modelling with empirical equations of Peleg and Page and phenomenological equations of Diffusion and Omoto-Jorge were considerad. The time and temperature affected significantly the hydration kinetics of grain sorghum. The Peleg and Diffusion models showed the best fitting for soaking and, therefore, these models were used to create generalized models. The effective diffusion coefficient of water during the grain sorghum hydration ranged from 2.02x10-11 to 6.34x10-11 m2.s-1 for BRS 310 and from 2.76x10-11 to 4.38x10-11 m2.s-1 for BRS 655 with activation energies of 11.52 and 31.21 kJ.mol-1, respectively.